Hybrid Method of Modal Analysis and Laser Shock Scanning to Visualize the Pyroshock Propagation in a Tension Joint - Yong-Woon Kim; Jae-Kyeong Jang; Jung-Ryul Lee; Hak-Seong Gim (Shock and Vibration)
The use of pyrodevices in the aerospace industry has been increasing because of their ability to implement separation missions with a small weight, for example, space launchers, spacecrafts, and missiles. During operation, pyrodevices generate pyroshock, which causes failures of electronic devices. Recently, a pyroshock simulation method using laser shock has been developed to evaluate the risk of pyroshock before flight mission. However, depending on the structure, the laser shock showed some difficulty simulating pyroshock in the low-frequency regime accompanying vibration. Therefore, in this study, we developed a hybrid method of numerical modal analysis and laser shock-based experimental simulation to visualize the pyroshock propagation in all the relevant frequency regimes. For the proof of concept of the proposed method, we performed experiments of explosive bolt-induced shock and pyrolock-induced shock in the open-box-type tension joint and compared the hybrid simulation results with actual pyroshock. From the results, we obtained the simulated time-domain signal with an averaged peak-to-peak acceleration difference (PAD) of 11.2% and the shock response spectrum (SRS) with an averaged mean acceleration difference (MAD) of 28.5%. In addition, we were able to visualize the simulation results in the temporal and spectral domains to compare the pyroshock induced by each pyrodevice. A comparison of the simulations showed that the pyrolock had an impulse level of 1/12 compared to the explosion bolt. In particular, it was confirmed that the pyrolock-induced shock at the near field can cause damage to the electronic equipment despite a smaller impulse than that of the explosive bolt-induced shock. The hybrid method developed in this paper demonstrates that it is possible to simulate pyroshock for all the frequency regimes in complex specimens and to evaluate the risk in the time and frequency domain.